Development Strategy of National Microsatellite Industry: Case Study of Indonesia - Chusnul Tri Judianto; Harianto Harianto; Agus Maulana (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2018)
Indonesia has larges archipelagic in the world, 13,466 islands with land area of 1,922,570 km2 and water area of 3,257,483 km2. Controlling and monitoring the huge area of Indonesia using satellite technology is a possible way to do and self reliance of space technology is the way to maintain satellite data security. Remote sensing data, telematics and communication were needed for many applications for people and industry. Development of satellite technology for developing country can be done since the utility of the Mechanical and Electronic Miniaturization System (MEMS) and Component of The Self (COTS) meet the microsatellite basic technology requirement. Indonesia has experience on microsatellite research for surveillance, remote sensing, ships monitoring and science through National Institute of aeronautics and Space (LAPAN). Sustainability of the microsatellite technology mastery need support from government regulation, commercial cooperation with private company and collaboration research with university for space technology innovation. By using the SWOT and Quantitative Strategic Planning Matrix (QSPM) method, this research identify and analyze the alternative strategy from external and internal factors and selects the appropriate and precise strategy for developing the microsatellite industry. The research shows that standardization of satellite system, product, metod, human resources and financial support with new investor using Public Private Partnership schemes as well as utilization of international cooperation with other country are the entrance for space industry. Keywords: Microsatellite, COTS, MEMS, QSPM